Pembelajaran Digital Guna Mendukung Guru Ekonomi Menjadi Pembelajar Kreatif Di Era Pandemi - Muazaroh Muazaroh; Supriyati Supriyati; Mochamad Nurhadi; Thomas Hanandry; Mochamad Al Hafidz (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
Due to the COVID-19 pandemic, learning in schools cannot be carried out face-to-face and must be done daring. Many teachers are not ready when it comes to teaching daring. Some teachers do not yet have the ability to use learning applications such as game Kahoot, Google Form, Google Classroom, Power Point presentation, create learning animations and others. This community service program is designed to equip teachers in MGMP economy (economic teacher meeting) to be able to give learning better and more interesting learning. Teachers are given training on the use of game kahoot, Google Form, Google Class Rooms, making interesting PPT and interesting learning videos. After the training on the use of these learning applications, the competence of teachers in digital learning increases as indicated by the work of game kahoot, google forms, google class room, PPT and learning videos. The output of this activity is the work of teachers in the form of kahoot game material, google form, google classroom, PPT and learning videos. In addition, the output of the activity is also in the form of activity videos uploaded on YouTube, publications in various mass media and training modules.